TB vaccines in clinical development - Ginsberg, AM; Ruhwald, M; Mearns, H; McShane, H (Elsevier, 2016)
The 4th Global Forum on TB Vaccines, convened in Shanghai, China, from 21e24 April 2015, brought together a wide and diverse community involved in tuberculosis vaccine research and development to discuss the current status of, and future directions for this critical effort. This paper summarizes the sessions on TB Vaccines in Clinical Development, and Clinical Research: Data and Findings. Summaries of all sessions from the 4th Global Forum are compiled in a special supplement of Tuberculosis.